Effect of Inorganic Fertilization Methods on Growth and Yield of Soybean on Alfisol - Ongko Cahyono; Suntoro Suntoro; Siti Maro'ah; Silfi Berliana Putri; Juan Yherin Wihangga (Universitas Sebelas Maret, 2025)
The ever-increasing demand for soybeans has not been matched by increased yields. This is partly due to farmers not fertilizing properly. Many farmers apply urea, SP36, KCl, or compound NPK fertilizers at doses that are inappropriate for the plants' needs. Many even fertilize haphazardly. Appropriate fertilization methods are needed. This study aims to determine the effect of some of fertilization methods on soybean growth and yield on Alfisol. This study used a completely randomized block design (RCBD) with five treatments and five replications. PT0 (no fertilizer), PT1 (Farmer's Method: Urea, SP36, and KCl), PT2 (Balanced Fertilization Method: Urea, SP36, and KCl), PT3 (Farmer's Method: NPK Compound Fertilizer), PT4 (Balanced Fertilization Method: NPK Compound Fertilizer). The results of this study show that inorganic fertilizers given in a balanced manner can increase soybean yields from 2.28 g/plant to 13.82 g/plant. The results of this study indicate that the best treatment method, PT2 (Balanced Fertilization Method: Urea, SP36, and KCl), is able to support plant growth and increase soybean yields.